Exploring Relationships between Professional Development and Teachers' Enactments of Project-Based Learning - JeanMarie Farrow; Sarah Schneider Kavanagh; Preeti Samudra (MDPI AG, 2022)
This paper examines whether teachers' prior professional development (PD) in Project-Based Learning (PBL) significantly related to teachers' enactments of PBL practices within the classroom. Teachers (N = 40) were recruited based on their commitment to enacting PBL in their classrooms. Teachers were surveyed regarding the extent to which they had experienced prior PD in PBL and asked to submit two videos of their classroom instruction. Videos were coded according to teachers' quality enactment of PBL practices during instruction. Results suggest that teachers who had prior PD in PBL enacted more structure-driven PBL practices (e.g., setting up and managing projects) and incorporated more collaboration practices. However, for other purpose-driven practices of PBL (e.g., supporting student choice, supporting students to make personal connections), teachers with prior PD were no different from teachers without prior PD. The results suggest that teachers may need more intensive and fine-grained, practice-based PD in purpose-driven PBL practices.